Randomized trial of pylorus-preserving vs. pylorus-resecting pancreatoduodenectomy: long-term morbidity and quality of life - Klaiber, Ulla; Probst, Pascal; Hüttner, Felix; Bruckner, Thomas; Strobel, Oliver; Diener, Markus K.; Mihaljevic, André Leopold; Büchler, Markus W.; Hackert, Thilo (Journal of gastrointestinal surgery, 2020)
The randomized controlled PROPP trial (DKRS00004191) showed that pylorus-resecting pancreatoduodenectomy (PR) is not superior to the pylorus-preserving procedure (PP) in terms of perioperative outcome, specifically in reduction of delayed gastric emptying. Non-superiority of PR was also confirmed in a recent meta-analysis of randomized controlled trials. However, long-term data on morbidity and quality of life after PP compared to PR are sparse. The aim of this study was to investigate long-term outcomes of patients included in the PROPP trial.